PENGGUNAAN RONGGIANG DALAM ACARA MALATI ANAK DI NAGARI AIA GADANG KABUPATEN PASAMAN BARAT - Fitri Nadhia, Fitri Nadhia; Tulus Handra Kadir (Universitas Negeri Padang, 2026)
This study aims to understand and reveal the use of ronggiang in the Malati Anak event in Nagari Aia Gadang, West Pasaman Regency. This type of research is qualitative research with a descriptive analytical method. The research instruments are self-conducted studies assisted with stationery, a camera and an audio recorder. Data is collected through library studies, observation, interviews and documentation. The steps for analysing data are data collection, data presentation and drawing conclusions. The results of the research indicate that the use of Ronggiang in the Malati Anak event in Nagari Aia Gadang, West Pasaman Regency, consists of Ronggiang and Malati Anak. Ronggiang elements consist of musical instruments, costumes, performers/actors, movements, songs, performance times and venues, and the audience. Musical instruments used include gandang, violin, microphone, horn, boto kaco, and tambourine. The costume worn consists of the Ronggiang art troupe's uniform and a sash. The Ronggiang performers consist of 12 members. The movements in this Ronggiang dance consist of three parts: the opening movement, the advancing greeting movement, and the advancing greeting movement with position changes. The songs performed are generally traditional Ronggiang art songs, including Pulau Pisang, Ronggiang Ka Berang, and Sikambang. The performance usually begins in the afternoon, with the venue depending on the host's agreement. This Ronggiang performance can be watched by all ages, from children, teenagers, adults, to the elderly, with the majority being elderly. The use of Ronggiang in Malati Anak consists of the Turun Mandi event and the wedding event. The Malati Anak Turun Mandi event is held by the bako side, usually performed by the child's grandmother, and is enlivened by Ronggiang music, while the Malati Anak wedding event is held by the bako side, usually performed by the child's amai, and the event takes place at their home with modest arrangements, only enlivened by Ronggiang art.